بنية الزمن في رواية حطب سراييفو - برمكي, عميار, مبروكة منال (University of El-oued, 2021)
الملخص: يتناول هذا البحث عنصر الزمن في رواية حطب سراييفو فجاء تحت عنوان بنية الزمن في رواية حطب بسراييفو لروائي الجزائر سعيد خطيبي في محاولة لبيان كيفية توظيف تقنيات الزمن في الرواية وقسمنا بحثنا إلى فصلين نظري يتضمن مفاهيم لغوية واصطلاحية وفلسفية للزمن وكذلك الأنواع وخصائص الزمن وحتى أهميته وتطبيقي ضع دراسة تطبيقية للزمن في الرواية حطب سراييفو حددنا فيه المفارقات الزمنية كنوع من المراوغة مع المتلقي ودرسنا الإيقاع الزمني وتطرقنا إلى علاقة الزمن مع باقي عناصر السرد وأنهينا عملنا بخاتمة تضمنه حوصلة لأهم النتائج Research summary: This research deals with the element of time in the novel firewood Sarajevo came under the title of the structure of time in the novel firewood Sarajevo by Algerian novelist Saeed Khatibi in an attempt to show how to employ the techniques of time in the novel and divided our research into two theoretical chapters that includes linguistic, idiomatic and philosophical concepts of time as well.
Keywords: بنية الزمن، حطب سراييفو، الزمن في الرواية الجزائرية.; The structure of time, the firewood of Sarajevo, time in the Algerian novel